New record of Cochlodiniam SP.in Perak coastal water of Peninsular Malaysia - Harun, Siti Nor Rahaida; Mohammad Noor, Normawaty; Saad, Shahbudin (2013)
Cochlodiniwn sp. has been reported to cause fish mortally around the world. In Malaysia this species has been recorded in Kota Kinabalu, Sabah, East of Malaysia. In Peninsular Malaysia several harmful algal bloom (HAB) species viz. Alexandrium spp., Pyrodinium bahamense var compressum and Gymnodinium catenatum have been recorded. To date no record of Cochlodiniurn sp. has been reported in this area. This study aim is to identify the present of Cochlodinium sp. in Peninsular Malaysia particularly in Perak coastal water. Samples were collected from 9 stations and Cochlodinium sp. was identified and enumerated under light microscopy. Nutrients i.e. nitrate, phosphate, silicate and ammonia were determined and physico-chemical parameters (pH, temperature, salinity)-were recorded in-situ. Result showed the present of Cochlodinium sp. at the cell density of 4.5 x l03cells/L. Salinity ranged from 17.8 to 30.7pss, pH ranged from7.2l to 8.4, temperature ranged from 30.80 to 32.08 0C Nutrients determined at this area showed a high concentration. This identification of Cochlodinium sp in Perak coastal waters indicates that Peninsular Malaysia will have problem related to Cochlodinium sp. in the future.